Naoxintong capsule for treating cardiovascular and cerebrovascular diseases: from bench to bedside - Zhang, Wei-jian; Chen, Rui-qi; Tang, Xuan; Li, Pei-bo; Wang, Jian; Wu, Hai-ke; Xu, Ning; Zou, Ming-fei; Luo, Sen-rong; Ouyang, Zi-qi; Chen, Zhi-kai; Liao, Xu-xing; et al. (Frontiers in Pharmacology, 2024)
Naoxintong Capsule (NXT), a renowned traditional Chinese medicine (TCM) formulation, has been broadly applied in China for more than 30 years. Over decades, accumulating evidences have proven satisfactory efficacy and safety of NXT in treating cardiovascular and cerebrovascular diseases (CCVD). Studies have been conducted unceasingly, while this growing latest knowledge of NXT has not yet been interpreted properly and summarized comprehensively. Hence, we systematically review the advancements in NXT research, from its chemical constituents, quality control, pharmacokinetics, to its profound pharmacological activities as well as its clinical applications in CCVD. Moreover, we further propose specific challenges for its future perspectives: (1) to precisely clarify bioactivities of single compound in complicated mixtures; (2) to evaluate the pharmacokinetic behaviors of NXT feature components in clinical studies, especially drug-drug interactions in CCVD patients; (3) to explore and validate its multi-target mechanisms by integrating multi-omics technologies; (4) to reevaluate the safety and efficacy of NXT by carrying out large-scale, multicenter randomized controlled trials. In brief, this review aims to straighten out a paradigm for TCM modernization, which help to contribute NXT as a piece of Chinese Wisdom into the advanced intervention strategy for CCVD therapy.